Formulation and characterization of acetate based ionic liquid in oil microemulsion as a carrier for acyclovir and methotrexate - Kandasamy, S. (Elsevier B.V., 2018)
Ionic Liquid (ILs) in oil microemulsions (IL/O MEs) have emerged as a potential carrier for transdermal drug delivery, particularly for sparingly soluble drug molecules, such as acyclovir and methotrexate. However, less attention was paid in the selection of non-toxic and biodegradable ILs. In this paper, we report new IL/O MEs with ammonium acetate ILs, which can dissolve acyclovir and methotrexate significantly. Microemulsions were composed of a mixture of nonionic surfactants, polyoxyethylene sorbitan monooleate (Tween-80), and sorbitan laurate (Span-20)/ILs/oil isopropyl myristate (IPM). Three ILs called 1-ethyl-3-methylimidazolium acetate (EMIMOAc), triethylammonium acetate (TEAOAc) and diethylammonium acetate (DEAOAc) were selected due to their non-toxic property. Based on the pseudo-ternary diagrams constructed, it was evident that Span-20 played the key role as a surfactant while Tween-80 acted as the co-surfactant, showing optimal dissolution of the ILs into the system prepared with a ratio of 1:3 (Tween 80:Span20). This binary mixture also depicted the lowest viscosity, which is favorable as a carrier agent in drug delivery. The incorporation of various ILs into microemulsions resulted in a particle size ranging from 11 to 39.7 nm at diverse drug loading capacity. The formulation with IL TEAOAc and IL DEAOAc displayed substantial drug carrying capacity and stability compared to the commercially available IL EMIMOAc loaded system. Â© 2017 Elsevier B.V.